2019
DOI: 10.1101/822429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Degradation of non-coding RNAs promotes recycling of termination factors at sites of transcription

Abstract: A large share of the non-coding transcriptome in yeast is controlled by the Nrd1-Nab3-Sen1 (NNS) complex, which promotes transcription termination of noncoding RNA (ncRNA) genes, and by the nuclear exosome, which limits the steady state levels of the transcripts produced. How global ncRNA levels impinge on cellular functions is a longstanding and important question. Here we show that degradation of ncRNAs by the exosome is required for freeing Nrd1 and Nab3 from the released transcript after termination. In ex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…In a similar way, it could be anticipated that a change in cellular state that causes alterations in mRNA or ncRNA processing would also feedback to impact genome-wide RNA maturation events through RBP availability. In agreement with this notion, recent work showed that stabilization of pervasive transcripts, such as CUTs in rrp6Δ cells, results in the sequestration of Nab3 and Nrd1 on these transcripts and titration of these RBPs away from other RNA substrates resulting in genome-wide transcription termination defects due to limited NNS availability ( 97 ). Similarly, it was proposed that the accumulation of Nab2 on mRNAs upon nuclear export failure prevents its recycling to newly generated RNA molecules, which leaves nascent transcripts vulnerable to nuclear decay ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 71%
“…In a similar way, it could be anticipated that a change in cellular state that causes alterations in mRNA or ncRNA processing would also feedback to impact genome-wide RNA maturation events through RBP availability. In agreement with this notion, recent work showed that stabilization of pervasive transcripts, such as CUTs in rrp6Δ cells, results in the sequestration of Nab3 and Nrd1 on these transcripts and titration of these RBPs away from other RNA substrates resulting in genome-wide transcription termination defects due to limited NNS availability ( 97 ). Similarly, it was proposed that the accumulation of Nab2 on mRNAs upon nuclear export failure prevents its recycling to newly generated RNA molecules, which leaves nascent transcripts vulnerable to nuclear decay ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 71%
“…To identify m 6 A-dependent mRNA targets bound by Pho92 during meiotic recombination, we performed an improved version of the UV-Crosslinking and analysis of cDNAs (CRAC) technique (Candelli et al, 2018; Granneman et al, 2009; Villa et al, 2020) on samples harvested at 5 hr in SPO medium. As required for the procedure, we used cells expressing an HTP (His 6 -TEV-ProteinA)-tagged version of Pho92 in WT and in ime4Δ / Δ strain as a control, to assess its specific binding to m 6 A-modified RNAs.…”
Section: Resultsmentioning
confidence: 99%
“…CRAC was performed essentially as described (Villa et al, 2020) with minor modifications. To facilitate later normalization between samples during dataset analysis, we used an internal “spike-in” extract of S. pombe expressing an RNA-binding protein fused to the HTP tag.…”
Section: Methodsmentioning
confidence: 99%
“…In rrp6Δ and other RNA exosome deletion mutant backgrounds, AS transcription is constitutively induced due to sequestration of the NNS (Nrd1-Nab3-Sen1) termination complex by stabilised non-coding RNAs. The NNS complex cannot be efficiently recycled to sites of transcription, inducing termination defects at non-coding RNA loci and resulting in their increased elongation frequency (48). To rule out possible indirect effects on transcription of the PHO5 gene due to gene deletion mutant backgrounds in which AS transcription is constitutively elongated, we turned to a system in which AS elongation is inducible.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we used the Anchor Away (AA) system to rapidly deplete Nrd1 protein from the nucleus by rapamycin treatment (50). Since Nrd1 belongs to the NNS surveillance system, its removal is expected to trigger transcriptional read-through of non-coding RNAs (49). Indeed, treatment of Nrd1-AA cells with rapamycin resulted in rapid induction of the PHO5 AS transcript production, clearly demonstrating that the NNS complex is important for its early termination in wild-type cells.…”
Section: Pho5 Gene Expression Kinetics Are Delayed Upon Induction In ...mentioning
confidence: 99%